2015
DOI: 10.1242/jcs.176081
|View full text |Cite
|
Sign up to set email alerts
|

Cadherin-11 endocytosis through binding to clathrin promotes cadherin-11-mediated migration in prostate cancer cells

Abstract: Cadherin-11 (Cad11) cell adhesion molecule plays a role in prostate cancer cell migration. Because disassembly of adhesion complexes through endocytosis of adhesion proteins has been shown to play a role in cell migration, we examined whether Cad11 endocytosis plays a role in Cad11-mediated migration. The mechanism by which Cad11 is internalized is unknown. Using a GST pulldown assay, we found that clathrin binds to the Cad11 cytoplasmic domain but not to that of E-cadherin. Using deletion analysis, we identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 46 publications
1
27
0
Order By: Relevance
“…Furthermore, the present study observed that the prognostic value may be largely enhanced by co-evaluating the expression of these three proteins in patients with OSCC. These results were in line with those of previous studies in other types of cancer (29)(30)(31), indicating that CDH6, CDH11 and CD44 may be either directly or indirectly involved in the metastasis of OSCC. Therefore, it is reasonable to combine the expression of these three proteins as predictive parameters for improved evaluation of the progression of OSCC.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, the present study observed that the prognostic value may be largely enhanced by co-evaluating the expression of these three proteins in patients with OSCC. These results were in line with those of previous studies in other types of cancer (29)(30)(31), indicating that CDH6, CDH11 and CD44 may be either directly or indirectly involved in the metastasis of OSCC. Therefore, it is reasonable to combine the expression of these three proteins as predictive parameters for improved evaluation of the progression of OSCC.…”
Section: Discussionsupporting
confidence: 92%
“…It is well-known that loss of E-cadherin and increased expression of N-cadherin is associated with tumor cell invasion in oral and ovarian cancer (28,29). By contrast, other mesenchymal-associated cadherins and adhesion factors, including CDH6, CDH11 and CD44, which have been proven to be able to interfere with epithelial cell-cell adhesion and to promote cancer cell invasion and metastasis, are often overexpressed in ovarian cancer (30)(31)(32). Until now, however, the precise role of the three factors in OSCC has not received a great deal of attention.…”
Section: Discussionmentioning
confidence: 99%
“…The proteomic study of urine in prostate cancer patients with a Gleason score of 6.9 ± 1.1 showed that LXR/RXR is activated and the signal of the acute-phase response is significantly downregulated [84]. Clathrin-mediated endocytosis is associated with the migration of prostate cancer cells [85]. The regulation of Rho on actin movement is significantly enriched after the tumor is palpable.…”
Section: Rm-1 Prostate Cancer-bearing Micementioning
confidence: 99%
“…In addition to the DEE and dileucine motifs, a recent study has exposed a new endocytic motif that is also potentially subject to regulation by p120. A mesenchymal cadherin that is expressed in osteoblasts (cadherin‐11) directly interacts with clathrin through a unique sequence, VFEEE, in the JMD of the cadherin tail . Mutation of this sequence inhibits endocytosis of the cadherin in PC3mm2 cells, a highly metastatic cell prostate tumor cell line .…”
Section: P120: Master Guardian Of Cadherin Endocytosismentioning
confidence: 99%
“…A mesenchymal cadherin that is expressed in osteoblasts (cadherin‐11) directly interacts with clathrin through a unique sequence, VFEEE, in the JMD of the cadherin tail . Mutation of this sequence inhibits endocytosis of the cadherin in PC3mm2 cells, a highly metastatic cell prostate tumor cell line . The VFEEE sequence is similar to the LxEx(D/E) clathrin‐binding box sequence found in the C‐terminal tail of arrestin3 .…”
Section: P120: Master Guardian Of Cadherin Endocytosismentioning
confidence: 99%